Implications of cyclophosphamide, methotrexate, and 5-fluorouracil chemotherapy on hippocampal-dependent cognition and gut microbiome - Corley, Christa; Swinton, Chase; McElory, Taylor; Sridharan, Bhavana; Thomas, Justin; Cronin, Bailey; Sridharan, Vijayalakshmi; Robeson, Michael S.; Allen, Antiño R. (Frontiers in Microbiomes, 2025)
Chemotherapy-induced cognitive impairment, also called “chemobrain”, has been heavily researched as a major side effect of cancer treatment. Although breast cancer has a 91% survival rate in the United States, this rate is significantly lower in developing countries. Cancer survivors often experience chemobrain, which can decrease their quality of life post-chemotherapy. The presented study evaluates potential mechanisms for long-term symptoms in cyclophosphamide, methotrexate, and 5-fluorouracil (CMF)-induced cognitive impairments and implications of CMF on the microbiome. Twelve-week-old C57/B6J female mice were treated with a combination of CMF once a week for 4 weeks. Spatial memory was tested with the Morris water maze. Hippocampal tissues were used to probe for immediate-early genes (IEGs) with Western blotting techniques. Fecal matter was collected to assess microbial community composition via 16S rRNA gene sequencing. In this study, we showed that chemotherapy impaired spatial memory during the Morris water maze trials and resulted in a significant decrease in IEGs c-Fos, Arc, and Zif286 expression. Comparing alpha-diversity, there were no significant differences identified among taxa within the CMF group compared to the saline group for Pielou’s evenness. However, beta-diversity qualitative metrics, Jaccard and Unweighted UniFrac, were significantly different. These results suggest that continual memory deficits may be associated with alterations in synaptic plasticity and long-term potentiation.